Program Bimbingan dan Konseling bagi Anak yang mengalami Speech Delay - Yulizar Abidarda; Akhmad Rizkhi Ridhani (Kuras Institute, 2022)
Children who experience speech delay or what is more commonly called speech delay are children with special needs. Children with special needs are children who differ in several ways from other normal people. That difference is physically, psychologically, cognitively, or socially late in reaching the maximum. The problems of children with special needs can be seen including hearing, visual, speech, mental and emotional disorders. Children who experience speech and language disorders are at risk of experiencing learning difficulties, difficulty reading and writing and will lead to less overall academic achievement, this can continue into young adulthood. The purpose of this research is to produce a product, namely a counseling program for children who experience speech delay. The methodology used is research and development research and development, which is a research method used to produce certain products and test the effectiveness of these products, in which in this study researchers only reached the product development stage. As for the data analysis technique used to analyze the problems that have been formulated previously, an interactive analysis model was used, which was developed by Miles and Huberman. The results of this study are the formulation of a counseling program for children who experience speech delay based on empirical and theoretical studies.